Three-dimensional Global Hybrid Simulation of Magnetosheath Jets at Mercury - Jin Guo; San Lu; Quanming Lu; Junyi Ren; Jiuqi Ma; James A. Slavin; Weijie Sun; Jun Zhong; Xinliang Gao; Rajkumar Hajra; Rongsheng Wang (The Astrophysical Journal Letters)
Plasma high-speed jets are common in Earth’s magnetosheath, and they significantly perturb the magnetosheath and affect the magnetosphere. The space environment of Mercury, characterized by the bow shock, magnetosheath, and magnetosphere, shares many similarities with that of Earth, so high-speed jets may also be formed in Mercury’s magnetosheath. Here we examine the formation of magnetosheath jets using a three-dimensional global hybrid simulation. The simulation results demonstrate that magnetosheath jets may be formed by the passage of upstream compressive structures through the bow shock. The number and size of the jets are significantly smaller than those at Earth because of Mercury’s smaller magnetosphere size. Under the impact of magnetosheath jets, Mercury’s magnetopause undergoes significant deformation up to $0.19\,R_{{\rm{M}}}$ ( ${R}_{{\rm{M}}}$ is Mercury’s radius). These simulation results are expected to be tested by the BepiColombo mission.